Neglected Case of Human Balantidiasis: Presumed as Antibiotic-Associated Diarrhoea - Sreska Shrestha; Priyatam Khadka (Case Reports in Infectious Diseases)
Background. Balantidiasis, due to its rare human incidence and nonspecific clinical presentations often neglected from the diagnosis considerations; however, a potent pathogen. Herein, we report a case of neglected balantidiasis presumed as antibiotic-associated diarrhoea. Case Presentation. A 27-year-old policeman presented in Sindhuli Hospital, with a chief complaint of epigastric pain, nausea, decreased appetite for several days, and loose stools (3-4 episodes per day). Previously, he was under antibiotic therapy (amoxycillin) for tonsillitis. The health post clinician made a presumptive diagnosis as the side effects of the antibiotics; however, the symptoms were not resolved. Complete blood cell count (CBC) was normal; renal function test (RFT) and liver function (LFT) were within the normal ranges. Ultrasonography of the abdomen and ECG (electrocardiogram) showed normal findings. However, on routine stool actively motile trophozoites of Balantidium coli (B. coli) were seen. He was treated successfully with metronidazole 750 mg tabs orally three times daily for 5 days. Conclusion. Protozoal infections, like balantidiasis, might be excluded from the diagnostic consideration in antibiotic-associated diarrhoea cases. Therefore, meticulous review of nonspecific clinical presentation and validation of an etiology with support of diagnostic tests are mandatory.